Immunogenicity of a Bivalent Adjuvanted Glycoconjugate Vaccine against Salmonella Typhimurium and Salmonella Enteritidis - Fiorino, Fabio; Rondini, Simona; Micoli, Francesca; Lanzilao, Luisa; Alfini, Renzo; Mancini, Francesca; MacLennan, Calman A.; Medaglini, Donata (Frontiers in Immunology, 2017)
Salmonella enterica serovars Typhimurium and Enteritidis are the predominant causes of invasive nontyphoidal Salmonella (iNTS) disease. Considering the co-endemicity of Salmonella Typhimurium and Enteritidis, a bivalent vaccine formulation against both pathogens is necessary for protection against iNTS disease, thus investigation of glycoconjugate combination is required. In the present work, we investigated the immune responses induced by S. Typhimurium and S. Enteritidis monovalent and bivalent glycoconjugate vaccines adjuvanted with alum only or in combination with CpG. Humoral and cellular, local and systemic, immune responses were characterized in two different mouse strains. All conjugate vaccines elicited high levels of serum IgG against the respective O-antigens (OAg) with bactericidal activity. The bivalent conjugated vaccine induced systemic production of antibodies against both S. Typhimurium and S. Enteritidis OAg. The presence of alum or alum+CpG adjuvants in vaccine formulations significantly increased the serum antigen-specific antibody production. The alum+CpG bivalent vaccine formulation triggered the highest systemic anti-OAg antibodies and also a significant increase in anti-OAg IgG in intestinal washes and fecal samples, with a positive correlation with serum levels. These data demonstrate the ability of monovalent and bivalent conjugate vaccines against S. Typhimurium and Enteritidis to induce local and systemic immune responses in different murine strains, and highlight the suitability of a bivalent glycoconjugate formulation, especially when adjuvanted with alum+CpG, as a promising candidate vaccine against iNTS disease.